(untitled) (Zaporizhzhia Historical Review, 2021)
In his article the author deals with the problem of cult practices in 1930-s. Forms and peculiarities of local cults and their structural elements are also described. In the article the author makes use of archive materials. The author concludes that local cult practices were an integral part of the system of power.